MRE11A Polymorphisms Are Associated With Subclinical Atherosclerosis and Cardiovascular Risk Factors. A Case-Control Study of the GEA Mexican Project - Vargas-Alarcón, Gilberto; Pérez-Hernández, Nonanzit; Rodríguez-Pérez, José Manuel; Fragoso, José Manuel; Cardoso-Saldaña, Guillermo; Vázquez-Vázquez, Christian; Ramírez-Bello, Julian; Posadas-Romero, Carlos; Posadas-Sánchez, Rosalinda (Frontiers in Genetics, 2019)
DNA damage and subsequent repair pathways have been involved in the initiation and progression of atherosclerosis. Meiotic recombination 11 homolog A (MRE11A) gene polymorphisms have been associated with the presence of myocardial infarction. We analyzed five MRE11A gene polymorphisms in 386 individuals with subclinical atherosclerosis and 1093 healthy controls. Under different models, the rs13447720 (Odds ratio = 0.646, Padditive = 0.009; Odds ratio = 0.636, Pdominant = 0.012; Odds ratio = 0.664, Pover-dominant = 0.025; Odds ratio = 0.655, Pcodominant1 = 0.021) and rs499952 (Odds ratio = 0.807, Padditive = 0.032; Odds ratio = 0.643, Pcodominant2 = 0.034) polymorphisms were associated with a lower risk of subclinical atherosclerosis. On the other hand, the rs2155209 polymorphism was associated with a reduced risk of having a coronary artery calcification score ≥ 100 Agatston units. The rs13447720, rs499952, and rs2155209 polymorphisms, as well as the haplotypes that included the five studied polymorphisms were associated with some clinical and metabolic parameters in both subclinical atherosclerosis and healthy individuals. Our results suggest that the rs13447720 and rs499952 polymorphisms are associated with a decreased risk of developing subclinical atherosclerosis, whereas the rs2155209 is associated with a lower subclinical atherosclerosis severity (coronary artery calcification < 100 Agatston units). MRE11A polymorphisms and haplotypes were associated with clinical and metabolic parameters.